Examining participant engagement in an information technology-based physical activity and nutrition intervention for men: the ManUp randomized controlled trial - Short, Camille E.; Vandelanotte, Corneel; Dixon, Marcus W.; Rosenkranz, Richard R.; Caperchione, Cristina; Hooker, Cindy; Karunanithi, Mohan; Kolt, Gregory S.; Maeder, Anthony; Ding, Hang; Taylor, Pennie; Duncan, Mitch J. (My University, 2014)
Background: Males experience a shorter life expectancy and higher rates of chronic diseases compared to their female counterparts. To improve health outcomes among males, interventions specifically developed for males that target their health behaviors are needed. Information technology (IT)-based interventions may be a promising intervention approach in this population group, however, little is known about how to maximize engagement and retention in Web-based programs. Objective: The current study sought to explore attributes hypothesized to influence user engagement among a subsample of participants from the ManUp study, a randomized controlled trial testing the efficacy of an interactive Web-based intervention for promoting physical activity and nutrition among middle-aged males. Methods: Semistructured interviews were conducted and audiotaped with 20 of the ManUp participants. Interview questions were based on a conceptual model of engagement and centered on why participants took part in the study, what they liked and did not like about the intervention they received, and how they think the intervention could be improved. Interview recordings were transcribed and coded into themes. Results: There were five themes that were identified in the study. These themes were: (1) users’ motives, (2) users’ desired outcomes, (3) users’ positive experiences, (4) users’ negative emotions, and (5) attributes desired by user. Conclusions: There is little research in the field that has explored user experiences in human-computer interactions and how such experiences may relate to engagement, especially among males. Although not conclusive, the current study provides some insight into what personal attributes of middle-aged males (such as their key motives and goals for participating) and attributes of the intervention materials (such as usability, control, and interactivity) may impact on user engagement in this group. These findings will be helpful for informing the design and implementation of future health behavior interventions for males.
Keywords: Qualitative; Intervention; Physical activity; Retention; Technology; Website; Engagement